Audit Manajemen Atas Fungsi Sumber Daya Manusia Pada PT Taspen (Persero) KCU Semarang - Etik Nur Aini Romdhoniyati; Heni Widyarti; Ardian Widiarto (JURNAL MANAJERIAL, 2021)
Background - Improve the quality and convenience of customers in social insurance services. PT. Taspen (Persero) KCU Semarang requires a management audit to evaluate and provide recommendations that need to be done to obtain effective human resources. interview with the Head of General and HR Section and several employees at PT. Taspen (Persero) KCU Semarang, the function of human resources (HR) at PT. Taspen (Persero) KCU Semarang can be said to have not been effective. Purpose – The purpose of this study was to determine the implementation of the eight Human Resource functions and the effectiveness of the Human Resource function at PT. Taspen (Persero) KCU Semarang. Design/ Methodology/ Approach - This research used descriptive qualitative. Data were collected using interview methods, questionnaires, and documentation studies. Data analysis used management audit with four stages, namely preliminary audits, review and testing of management controls, detailed audits, and reports. Result and discussion - Five of the eight HR functions at PT. Taspen (Persero) KCU Semarang has been implemented effectively, namely (1) performance appraisal, (2) career development, (3) reward and compensation system, (4) employee protection and (5) employment relations. Meanwhile, the three functions that have not been implemented effectively include (1) orientation and placement, (2) training and development, and (3) termination of employment. Conclusion - The eight management functions have not fully achieved the expected effectiveness in accordance with the audit indicators in the human resources function. Research Implication – The implications in research for PT Taspen (Persero) KCU Semarang can be used as material for consideration and evaluation of three HR functions that have not been implemented effectively, so that they can be used for decision making to improve HR management performance, especially in the general section.